Integrin signaling in tumor biology: mechanisms of intercellular crosstalk and emerging targeted therapies - Yifan Li; Shantong Peng; Jiatong Xu; Wenjie Liu; Qi Luo (PeerJ)
Integrins, a family of transmembrane cell adhesion receptors, mediate intercellular and cell–extracellular matrix crosstalk via outside-in and inside-out signaling pathways. Integrins, categorized into 24 distinct combinations of α and β subunits, exhibit tissue-specific expression and perform unique or overlapping roles in physiological and pathophysiological processes. These roles encompass embryonic angiogenesis, tissue repair, and the modulation of tumor cell angiogenesis, progression, invasion, and metastasis. Notably, integrins are significant contributors to tumor development, offering valuable insights into the potential of integrin-targeted diagnostics and therapeutics. Currently, there are various preclinical and clinical trials aiming to harness integrin antagonists that are safe, efficacious, and exhibit low toxicity. Owing to the functional redundancy across integrin types and the complexity of the mechanisms of integrin-mediated multiple key processes associated with tumor biology, challenges exist that impede advancements in integrin-targeted therapy. Nevertheless, innovative strategies focused on integrin modulation represent significant breakthroughs for improving patient care and promoting comprehensive insights into the underlying mechanisms of tumor biology. This review elucidates the impact of integrins on three distinct cell types in multiple key processes associated with tumor biology and explores the emerging integrin-targeted therapeutic approaches for the treatment of tumors, which will provide ideas for optimal therapeutic approaches in the future.